Pengembangan E-Book Interaktif Berbasis Kearifan Lokal untuk Pembelajaran Keterampilan Membaca Teks Berita SMPN 34 Padang - Etri, Gia Juli; Amir, Amril (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
The background to this research is that technological developments are increasingly rapid in human life in various fields, one of which is education. This type of research uses Research and Development (R&D). The development model used in this research is a 4-D model consisting of four stages, namely: 1) define, 2) design, 3) develop, and 4) disseminate. This research used a questionnaire instrument data collection technique which was distributed to class VIII students of SMP Negeri 34 Padang. Based on the results of the student needs questionnaire analysis, the results showed that 83% of students needed digital learning media. There are 3 aspects in the research questionnaire, namely student needs in the learning process aspect which obtained a percentage of 84%, student needs in the learning media aspect 84%, and student needs in the teaching material content aspect 80%. The average percentage result for all aspects is 83%, so it falls into the